The Exploration of Skilled and Less-Skilled EFL Graduate Students' on L1 and L2 Writing Strategies - Syaadiah Arifin (Jurnal Pendidikan Indonesia, 2020)
This study aims to analyze the similarities, differences, and transferability of students' writing strategies in L1 (Indonesian) and L2 (English). Data were obtained from four participants majoring in English Education, two males and two females, which were categorized into skilled and less-skilled writers. The data were collected for four months using various methods, namely think-aloud protocols (TAPs), retrospective and semi-structured interviews, observations, and written drafts. The result showed that students employed similar personal strategies while writing in Indonesian (L1) and English (L2). This means that they transferred L1 strategies to L2 with some variances and similarities. The skilled writers viewed writing as a cyclical process of planning, writing, reading/rereading, rehearsing, and revising their texts. Meanwhile, less-skilled writers tended to employ linear and less recursive strategies. Furthermore, subsequent studies need to be conducted using these research findings and suggestions.